HSC-derived exosomal miR-122-5p inhibits EMT and fibrosis of intrahepatic biliary epithelial cells to alleviate primary biliary cholangitis - Zhang, Yaqin; Chen, Ruofei; Yang, Xueqing; Qian, Long; Shen, Bing; Shuai, Zongwen (Frontiers in Immunology, 2025)
IntroductionPrimary biliary cholangitis (PBC) is a chronic autoimmune-mediated cholestatic liver disease that can progress to cirrhosis and liver failure. Intrahepatic biliary epithelial cells (IBECs) are the primary targets of early injury in PBC. Our previous studies have shown that exosomes derived from hepatic stellate cells (HSCs) deliver miR-122-5p to regulate the expression of human IBEC inflammatory factors via the p38 MAPK signaling pathway. The purpose of this study was to investigate the therapeutic potential and molecular mechanism of HSC-derived exosomal miR-122-5p in PBC.MethodsThe effects of exosomal miR-122-5p in inhibiting apoptosis, epithelial–mesenchymal transition (EMT), and fibrosis were evaluated in lipopolysaccharide (LPS)-induced human IBEC models, and its anti-inflammatory and anti-fibrotic effects were measured in dnTGF-βRII mouse models. A variety of analytical procedures, such as flow cytometry, Cell Counting Kit-8 (CCK-8), RT-qPCR, ELISA, co-culture, Western blotting, immunofluorescence, gene transfection, immunohistochemistry, and several staining methods (H&E and Masson), were used to evaluate the effectiveness and mechanisms of these methods.ResultsThe results from clinical data showed that exosomal miR-122-5p was correlated with liver function, and when combined with gp210 and sp100 antibodies, it could improve the sensitivity of PBC diagnosis. The results from in vitro experiments showed that exosomal miR-122-5p promoted the proliferation and inhibited the apoptosis, EMT, and fibrosis indicators of IBECs via the p38 MAPK signaling pathway. Dual luciferase reporter assay indicated that tumor necrosis factor receptor superfamily (TNFRSF) 19 is a specific target of miR-122-5p and reduces ASK1 levels. The co-immunoprecipitation (Co-IP) experiment further indicates the interaction between TNFRSF19 and ASK1. In vivo results indicated that the degrees of inflammatory infiltration and fibrosis in liver tissues of both PBC patients and model mice were more severe than those of normal controls and were then alleviated with exosomal miR-122-5p treatment.ConclusionIn conclusion, exosomal miR-122-5p alleviates liver pathology in PBC by targeting the TNFRSF19/ASK1/p38 MAPK axis, highlighting its potential as both a diagnostic biomarker and a therapeutic target for PBC.